Compromising quality parameters lead to fallout: a study of de-indexing of research journals - (Corresponding Author), Ramesh Pandita; Singh, Shivendra (Malaysian journal of library & information science, 2023)
The study aims to investigate the number of journals de-indexed by Scopus during the last two decades, specifically, from 2000 through 2019. Data for the study were retrieved from SCImago, a Scopus database. The scope of the study is global, covering all the 27 major subject disciplines categorized in Scopus. A total of 6059 research journals were found to be de-indexed from Scopus up until 2019, accounting for 18.61 percent of the total journals indexed in Scopus till date. Among the total de-indexed journals, 2311 (38.14%) journals were de-indexed from the period between 2000 and 2019. A steady decline in the de-indexing of journals has been observed after the year 2010. Among the top 20 countries with the highest number of de-indexed journals, it was found that 90.11 percent of journals have been de-indexed from these countries altogether. The United States stands out as the leading country, contributing to nearly one-third of the total de-indexed journals worldwide, with Medicine (44%) being the leading subject area in the de-indexed journals. On a national level, Sweden takes the lead, recording the highest de-indexing rate of 40.70 percent of journals. Following standard publishing parameters in publishing research results is of utmost importance for several reasons, with the primary one being dissemination of genuine and authentic research for the larger benefit of society. Any compromise with the quality of published research must be addressed seriously, and if necessary de-indexing a journal as a punitive measure should be considered appropriate and welcomed.